THE USE OF CODE-SWITCHING IN SOCIAL MEDIA (LINE) BY ALUMNI OF SMAN SUMATERA SELATAN - Merta Septiani; Ismail Petrus; M Yunus (Sriwijaya University Learning and Education International Conference, 2018)
The phenomenon of code-switching is an important issue in bilingualism. Many researchers have investigated its value in formal classroom teaching and learning activity. Code-switching in this study refers to the alternation of two languages, English and Indonesians, which happens during a conversation in social media. This study identified types and topics as well as investigated the factors that affect code switching in the online chatroom among 96 bilingual young adults. Cross-sectional survey design was used in this study. The data were collected through review of chats, questionnaire, and interview. Later, the data were analysed by using the statistics. The findings from the study revealed that the alumni of SMAN Sumatera Selatan mostly used intrasentential code- switching (67%), were interested in the topics of social, health, economics, politics, education, and technology, and their primary factor or reason of using code-switching was avoiding misunderstanding (75%). Other noted factors were: being easier to speak in own language (52.5%), not knowing the English words (28.7%), not similar words in L1/L2 (27.5%), filling the stopgap (25%), adding emphasis (25%), conveying intimacy (18.8%), and privacy (18.8%). In addition, the data revealed that the factors and the topics had a significant connection. Finally, codeswitching can be a useful strategy in online interaction if the aim is to maintain solidarity in an efficient way.